Modular Synthesis of Methyl-Substituted Novel Psoralen N-Hydroxysuccinimide Esters and Evaluation of DNA Photocrosslinking Properties of the Corresponding Triplex-Forming Oligonucleotide Conjugates - Mikame, Yu; Maekawa, Nagisa; Kimura, Soichiro; Nakao, Juki; Yamayoshi, Asako (Synlett, 2024)
Psoralen-conjugated triplex-forming oligonucleotides (Ps-TFOs) have been used to induce DNA mutations or to suppress gene expression through the formation of crosslinked products with DNA in a sequence-specific manner. Psoralen can crosslink with DNA at its furan-ring and/or pyrone-ring side, yielding either a monoadduct or diadduct (interstrand crosslinking) product. The differences in the crosslinked structures of Ps-TFOs with the target DNAs are closely related to the changes in the biological outcomes induced by the Ps-TFOs. However, only a few reports have discussed the photocrosslinking properties of Ps-TFOs. The photocrosslinking properties of Ps-TFOs with structurally diverse psoralen derivatives remain elusive. Herein, we report the modular synthesis of novel methyl-substituted psoralen N-hydroxysuccinimide (NHS) esters. By using these esters, the effect of the methyl substituent of psoralen on the photocrosslinking of the corresponding Ps-TFOs was examined. The amount of the diadduct product was significantly reduced in the presence of methyl substituents at the C-3 and C-4 positions, while the total amount of photocrosslinking product was maintained. This work demonstrates the possibility of controlling the crosslinked product of Ps-TFOs by introducing methyl groups into psoralen: this ability to manipulate the product is an important factor in the biological applications of Ps-TFOs.
Keywords: psoralen; triplex-forming oligonucleotides; modular synthesis; substituent effect; photocrosslinking; DNA crosslinking